2003
DOI: 10.1097/00007632-200307150-00022
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The delayed onset of obliquus internus abdominis, multifidus, and gluteus maximus electromyographic activity of the supporting leg during hip flexion, in subjects with sacroiliac joint pain, suggests an alteration in the strategy for lumbopelvic stabilization that may disrupt load transference through the pelvis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…The gluteus maximus activation was also delayed, suggesting an inability to compress and stabilize the sacroiliac joint and pelvis with associated lower extremity movement. Overall, these studies 28,29,32 illustrate alterations in muscle recruitment, suggesting that deficiencies in core stabilization and load transfer muscles may be related to lower extremity function and injury.…”
Section: Injury Riskmentioning
confidence: 83%
See 2 more Smart Citations
“…The gluteus maximus activation was also delayed, suggesting an inability to compress and stabilize the sacroiliac joint and pelvis with associated lower extremity movement. Overall, these studies 28,29,32 illustrate alterations in muscle recruitment, suggesting that deficiencies in core stabilization and load transfer muscles may be related to lower extremity function and injury.…”
Section: Injury Riskmentioning
confidence: 83%
“…12,13,20,28,29,32 The transversus abdominus and multifidus—local stabilizer muscles—display changes in recruitment 12,13,20,28,29,32 and morphology 44 that limit their ability to effectively stabilize the spine and provide accurate proprioceptive information. Hodges et al examined core muscle recruitment patterns during upper 29 and lower 28 extremity movements in LBP patients compared with healthy controls.…”
Section: Injury Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…If the GM works inappropriately during gait, it can cause back pain, resulting from a lack of shock-absorption at the sacroiliac joint2 ) , and Hungerford et al3 ) suggested that the activity of GM in the legs of patients with sacroiliac joint pain is delayed, and that the biceps femoris shows early activation to compensate for this delay. Moreover, individuals with limited movement of GM show fast movement of the hamstring muscles (HAM) and erector spinae muscles for better stability of their back4, 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…However, because the structure of the spine is more unstable than those of other bones, the roles of the deep muscles are particularly important for spinal stabilization1 ) . Representative deep muscles of lumbar stabilization include the transversus abdominis muscle (Tra) and the multifidus muscle2 ) . The fact that Tra greatly contributes to lumbar stabilization has been proven by many studies, and the importance of this muscle has been established3 ) .…”
Section: Introductionmentioning
confidence: 99%